Inflow and outflow from the accretion disc of the microquasar SS433: UKIRT spectroscopy - Perez, S; Blundell, K (2009)
A succession of near-IR spectroscopic observations, taken nightly throughout an entire cycle of SS433's orbit, reveal (i) the persistent signature of SS433's accretion disc, having a rotation speed of ~500 km/s, (ii) the presence of the circumbinary disc recently discovered at optical wavelengths by Blundell, Bowler and Schmidtobreick (2008) and (iii) a much faster outflow than has previously been measured for the disc wind. From these, we find a much faster accretion disc wind than has noted before, with a terminal velocity of ~1500 km/s. The increased wind terminal velocity results in a mass-loss rate of ~10e-4 M_sun/yr. These, together with the newly (upwardly) determined masses for the components of the SS433 system, result in an accurate diagnosis of the extent to which SS433 has super-Eddington flows. Our observations imply that the size of the companion star is comparable with the semi-minor axis of the orbit which is given by (1-e^2)^(1/2) 40 R_sun, where e is the eccentricity. Our relatively high spectral resolution at these near-IR wavelengths has enabled us to deconstruct the different components that comprise the Brackett-gamma line in this binary system, and their physical origins. With this line dominated throughout our series of observations by the disc wind, and the accretion disc itself being only a minority (~15 per cent) contribution, we caution against use of the unresolved Brackett-gamma line intensity as an "accretion signature" in X-ray binaries or microquasars in any quantitative way.